Optimization of Rebaudioside A extraction from stevia leaves using response surface methodology - Kalaiarasan, Muthusamy; Mimi Sakinah, A. M. (IOP Publishing, 2020)
Rebaudioside A or Reb A is an extractable component from stevia leaves or scientifically known as Stevia rebaudiana. Reb A is famous for its exceptional sweetness and widely used as a non-caloric sweetener. Its potential widespread use requires an easy and effective extraction method. In this study, extraction of Reb A from stevia leaves with parameters such as temperature, material ratio and extraction time were investigated. Time of extraction were 1, 1.5, 2, 2.5 and 3 hours. Temperature was varied at 400C, 450C, 500C, 550C and 600C. Material ratio was 1:5, 1:10, 1:15, 1:20 and 1:25. Then, using Design Expert software, the ranges of the parameters were entered in the Central Composite Design (CCD) to create 20 different combinations of parameters for extraction. After executing the experiments, the yield of Reb A obtained was keyed in Response Surface Methodology (RSM) for optimization. Finally, the optimum condition was tested and validated by calculating the percentage error. Since the percentage error was less than 10%, the optimum condition, which is, 350C, 1:6 material ratio and 5 hours of extraction was accepted